MULTIPLE SPOT URINE SAMPLING IS MORE PRECISE, ACCURATE AND SIMPLE COMPARED TO 24 HOURS COLLECTION FOR ESTIMATING SODIUM EXCRETION. (June 2018) - Salice, G.; Ardissino, G.; Ghiglia, S.; Perrone, M.; Tel, F.; Mezzopane, A.; Piantanida, A.; Lettera, T.; Mehmeti, F.; Savina, P.; Grimaldi, G.; Xaiz, L.; et al.
Abstract : Objective: The 24 hours urinary collection (24-hrsUC)that is the standard of care to estimate Sodium (Na) intake in the management of HPT, can be inaccurate because of errors in time and/or volume, unpractical and when done during weekends, not representative of usual Na intake. Multiple spot urine sampling is not affected by any of the above mentioned sources of error. We hypothesized that the mean urinary Sodium-to-urinary Creatinine ratio (uNa-to-uCrR) of multiple spot samples, collected in different days, is more precise and accurate for estimating the average Na excretion compared to 24-hrsUC. Design and method: A total of 180 urine samples (1 for each voiding) and the related 30 24-hrsUC performed in different days in 4 heathy subjects (up to nine voiding per day) were collected. For the purpose of comparison, uNa excretion in mEq/Kg/day from each sample was derived multiplying by 2 each uNa-to-uCrR (the mean conversion constant obtained from all ratios as determined from 24-hrsUCs). We calculated Lin's correlation coefficient, mean bias, and 95% limits of agreement (LOA), of uNa for: the single 24-hrsUC and 1000 random samples of means of 4 spot urine samples (1 per subject in 4 different days) using the individual overall 24-hrsUC average as reference in both. Statistical analysis was performed using Stata 15 Results: 1) The single 24-hrs-UC urine collections showed a Lin's coefficient of 0.64, with 95% limits of agreement (LOA) of + 1.65 mq/Kg/die (difference between upper and lower LOA: 3.29). 2) In the 1000 random samples the average Lin's coefficient was 0.72 (SE: 0.23). Mean bias and 95% LOA were 0.21, −1.06, and 1.48, respectively, while mean difference between upper and lower LOA was 2.54. Lin's coefficient was greater than 0.64 in 76.6% of samples. Difference between upper and lower LOA was smaller than 3.29 in 81.0% of samples t The mean uNa-to-sCrR from 4 spot samples estimates Na excretion more precisely and accurately than a single 24-hrsUC. providing a more reliable estimate in as many as 81% determinations as compared to only 19%